Discrete element modeling of shear wave propagation using bender elements in confined granular materials of different grain sizes. (September 2020) - Gu, Xiaoqiang; Liang, Xiaomin; Shan, Yao; Huang, Xin; Tessari, Anthony
Abstract: The discrete element method is used to simulate shear wave propagation resulting from bender element tests in confined granular materials. The effects of particle size, wave travel distance, confining pressure, void ratio, input frequency, and adopted damping methods on the output frequency and calculated shear wave velocity are systematically analyzed. The research findings indicate that the output frequency first increases with the input frequency until it reaches a threshold value. This output frequency threshold decreases with an increase in wave travel distance before reaching a constant value, while it decreases linearly with an increase in particle size. The research also shows that when the ratio of the wave travel distance to the mean particle size exceeds 20, the ratio of the wavelength to the equivalent mean particle size is consistently close to 10. It is suggested that the viscous and the local damping ratios should be less than 5% and 20%, respectively, for wave propagation simulations. Moreover, the research endeavor found that the shear wave velocity correlates with the coordination number of the specimen from a particulate perspective. These findings advance the fundamental understanding of wave propagation and provide valuable guidance for simulating wave propagation using the discrete element method.